Compton polarimeter for 10-30 keV x rays - Weber, Sebastian; Beilmann, Christian; Shah, Chintan; Tashenov, Stanislav (Review of scientific instruments, 2015)
We present a simple and versatile polarimeter for x rays in the energy range of 10-30 keV. It uses Compton scattering in low-Z materials such as beryllium or boron carbide. The azimuthal distribution of the scattered x rays is sampled by an array of 12 silicon PIN diodes operated at room temperature. We evaluated the polarimetry performance using Monte-Carlo simulations and show experimental results.